La promesse du bonheur : introduction - Sara Ahmed (Genre, Sexualité et Société)
The work of the queer phenomenologist Sara Ahmed questions the injunctions and identifications produced by affects in order to consider the critical power of feminist, queer and black movements. In the wake of a work on cultural politics of emotions (2004), she lays the fundations of a critic of the thinking of happiness. This introduction of The Promise of Happiness challenges what does the desire of happiness do. Drawing upon classical philosophy, psychoanalytical theory and a critique of the contemporary discourse of positive psychology, she questions the positive nature of happiness. She offers a powerful demonstration of how happiness is used to justify a certain form of oppression and to make desirable specific social norms: the call for happiness aligns people with objects and life choices conventionally associated with happiness, notably specific family choices. Thus the « happiness duty » becomes a disciplinary technique. Sara Ahmed delivers here a call to think alternative trajectories and definitions of what can constitute a good life.